Research Progresses of Circulating Tumor Cells in Diagnosis and Treatment of Early Lung Cancer - Xinchun DUAN; Zhidong LIU; Shaofa XU (Chinese Journal of Lung Cancer, 2017)
As one of the important liquid biopsies, circulating tumor cells (CTCs) shows more and more clinical values in the treatment of lung cancer such as diagnostic screening, treatment evaluation, postoperative monitoring, and prognosis predicting etc. A large number of small pulmonary nodules patients are detected when screening the high risk population of lung cancer. However, small lung nodules are not equal to lung cancer, and 90%-95% of them are benign lesion, therefore, to accurately and correctly differentiate whether it is benign or malignant when patients firstly detected and treat a small pulmonary nodule is become a new opportunity and challenge for clinician. With the improvement of CTCs detection technology, whether it will play an important role in early differential diagnosis of lung cancer. And whether it will have clinical significance to early lung cancer surgery operations. These require further researches and explorations so as to achieve clinical transformation in the future.